DIGESTIPEDIA-WEB: Learning media innovation to improve critical thinking skills - Rizhal Hendi Ristanto; Dwi Angelita; Rizki Awalia; Feni Oetari; Mieke Miarsyah (STKIP Persada Khatulistiwa Sintang, 2023)
Developing students' critical thinking skills in learning was an effort to improve learning outcomes. However, critical thinking skills were still not fully developed. The development of Digestipedia-web or website-based media was expected to improve students' critical thinking skills. The purpose of this study was to examine the feasibility and quality of Digestipedia-web media in improving critical thinking skills. This study used the Research and Development method with the ADDIE model. The research was carried out in November 2022. The developed media was tested for feasibility in terms of material, media and language by two expert validators. The effectiveness of the developed media was tested on 35 students at SMAN 18 Tangerang Regency, Indonesia. The overall results of the media test were categorized as valid and feasible. The results of the students' post-test scores were higher than the pre-test scores. The results of the media effectiveness test with the N-Gain test obtained the medium category. The conclusion of this study showed that Digestipedia-web was valid and feasible to use as a learning medium and can improve critical thinking skills in digestive system material.